Analysis of Road Conditions Affecting Transport Flow Using Throwable Roads (Texas Journal of Engineering and Technology, 2022)
In this article discussed the road surface elements and data analysis of environmental impact assessment. The main purpose of work is to give recommendations to improve the working conditions and given scientific conclusions which will be used in future road design and highway projecting.